Leading through CRISIS and COVID; It’s Not What You Think - Christopher Jochum (Academic Chairpersons Conference Proceedings, 2022)
This interactive workshop will use the acronyms CRISIS and COVID to help participants identify and refine their leadership styles and departmental culture during times of crisis. Participants will learn how to apply the CRISIS and COVID models with their respective departments to better identify their mission and develop growth initiatives.
Keywords: Crisis leadership; Leadership development; Leadership philosophy; Departmental culture; Departmental improvement